2006
DOI: 10.1103/physrevb.74.235405
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transmission with coaxial nanoapertures: Role of cylindrical surface plasmons

Abstract: We simulate the optical fields and optical transmission through nanoarrays of silica rings embedded in thin gold films using the finite-difference-time-domain method. By examining the optical transmission spectra for varying ring geometries we uncover large enhancements in the transmission at wavelengths much longer than the usual cutoffs for cylindrical apertures or where the usual planar surface plasmons or other periodic effects from the array could play a role. We attribute these enhancements to closely co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 31 publications
5
44
0
Order By: Relevance
“…[ 47 ] For AAAs, Haftel et al have theoretically investigated the role of CSPs in enhanced optical transmission and found that the resonant CSP wavelength increases as the annular aperture size decreases. [ 48 ] Our calculation results clearly confi rmed a similar trend. It is worth mentioning that for the PSP-induced peaks, the calculated and experimental data follow a general trend although there is a slight offset, while for the CSP-induced peaks, the experimental results deviate largely from the calculated data.…”
Section: Op133supporting
confidence: 79%
“…[ 47 ] For AAAs, Haftel et al have theoretically investigated the role of CSPs in enhanced optical transmission and found that the resonant CSP wavelength increases as the annular aperture size decreases. [ 48 ] Our calculation results clearly confi rmed a similar trend. It is worth mentioning that for the PSP-induced peaks, the calculated and experimental data follow a general trend although there is a slight offset, while for the CSP-induced peaks, the experimental results deviate largely from the calculated data.…”
Section: Op133supporting
confidence: 79%
“…[1][2][3][4][5][6] Such nanostructures provide additional functionalities compared to simple circular apertures in terms of very high absolute transmission related to specific waveguided modes in annular apertures, absent in simple circular holes. Coupled to surface plasmon polariton modes on metal film interfaces, these modes provide a possibility to achieve high transmission, field enhancement as well as high extraction efficiency of light trapped in the substrates.…”
mentioning
confidence: 99%
“…There have been studies considering AAA with glass as a substrate, in the near-infrared, and the visible regime. [1][2][3][4][5][6] Recently, it was experimentally demonstrated an enhanced transmission around 90%. 9 When glass is used a substrate, it is possible to take advantage of the resonance associated with the cutoff of the TE 11 mode of individual annular apertures.…”
mentioning
confidence: 99%
“…The next lowest order mode can have a cutoff that is modified by adjusting the inner radius, and this influences the transmission, as described in the previous section. For real metals, the cutoff of the corresponding TE 11 -like gap-mode is influenced by the metal response as well as the gap and it has been referred to as the cylindrical surface plasmon (CSP) mode [83][84][85]. Field intensity enhancements of 600 have been calculated inside the annular holes [86].…”
Section: Hole-shape: Basis Effectsmentioning
confidence: 99%